HEALTH RESORT DAN SPA DENGAN PENDEKATAN ARSITEKTUR TROPIS - Cathrine Aurellia Ivana; Affrilyno Affrilyno; Bontor Jumaylinda BR Gultom (JMARS: Jurnal Mosaik Arsitektur, 2023)
Changes in lifestyle with increasingly crowded routines make humans pay less attention to physical conditions that can cause stress. So that from this potential, the idea of planning a design that prioritizes "health” in tourism and "health" can also be found in beautiful views around the area. The location is located in Singkawang City, which is in the waterfront area (Palm Beach) Jl. Pasir Panjang Beach, Sedau Village, Singkawang Selatan District which is a tourism area, and the soil type is soft soil. The selection of the structure used applies a concrete pile foundation. Health resorts and spas located in the tropics use a design approach using tropical architecture to provide visitors with comfort. This effort is made by implementing placement and orientation facing the main view and spreading so that each building gets wind circulation and is supported by mass compositions and the use of local materials, the use of natural ventilation, skylights, and sun shading. Visitors consist of individuals, couples, families, and other general groups who do not stay overnight by providing lodging facilities that are not only for resting but have health service facilities (health resort) like resort standards, resort suite, and resort family suite, treatment facility (health spa), restaurants, and wedding venues. The design method consists of the stages of an idea, information, analysis, synthesis, evaluation, and optimization.